2019
DOI: 10.1002/anzf.1364
|View full text |Cite
|
Sign up to set email alerts
|

TheKINDProgram for Adolescent Family and Dating Violence

Abstract: Adolescent relational violence has significant and pervasive impacts for young people's current and future relationships. It is known that there is a cross‐over between adolescent family violence and other offending behaviour, meaning there is a need for youth justice systems to recognise and respond to these forms of violence. This paper outlines a pilot intervention, the KIND Program, run in Youth Justice South Australia, and aimed at intervening with adolescent family and dating violence. KIND aims to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Due to the complexities of the adolescents and families who experience AVTP (e.g. mental health, other offending, drug and alcohol use), one on one and family intervention is often more appropriate than group programmes as it can prioritise the exploration of each individual family member’s unique experiences and be tailored to their history and trauma (Holt, 2012; Moulds et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complexities of the adolescents and families who experience AVTP (e.g. mental health, other offending, drug and alcohol use), one on one and family intervention is often more appropriate than group programmes as it can prioritise the exploration of each individual family member’s unique experiences and be tailored to their history and trauma (Holt, 2012; Moulds et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moulds et al (2019) similarly report factors such as mental health, housing precarity, trauma and substance use affected the program progress of some participants. Only one study reported participants of Indigenous background (Moulds et al, 2019). Omer and Lebowitz (2016) reported findings from 13 studies with a range of mental health issues and one with high functioning autism.…”
Section: Resultsmentioning
confidence: 89%
“…A total of six distinct interventions are identified in this review (see Table 1). Four studies investigate three different interventions within the criminal justice system (Correll et al, 2017; Gilman & Walker, 2020; Moulds et al, 2019; Nowakowski & Mattern, 2014). The settings of the other interventions were not specified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations